Fixed Exchange Rates and the Autonomy of Monetary Policy : The Franc Zone Case - Veyrune, Romain (IMF Working Papers; Working Paper ;, 2007)
This paper compares monetary policy of currency boards with that of the franc zone during the period 1956-2005. It concludes that monetary policy in the zone was more autonomous than under a currency board, even though both systems faced the same exchange rate constraint. So far, the contingency line provided by the French treasury and capital controls have allowed the zone to combine a fixed exchange rate and a relatively autonomous monetary policy. Financial development and zone enlargement would challenge this relative autonomy for two reasons: (1) the potential cost to the French treasury would increase; and (2) residents would potentially be able to avoid capital controls. For the zone to maintain its fixed exchange rate, close targeting of foreign reserves would become important.